2020
DOI: 10.3390/ma13235524
|View full text |Cite
|
Sign up to set email alerts
|

Study of Machining Process of SiCp/Al Particle Reinforced Metal Matrix Composite Using Finite Element Analysis and Experimental Verification

Abstract: In this paper, a two-dimensional orthogonal cutting simulation model of SiCp/Al composite was established. The geometry and material constitutive model of the particle, the matrix, and the interface layer have been modeled respectively. In view of the distribution of the particles in the matrix, this paper proposed respectively a two-dimensional particle random distribution to simulate particles randomly distributed in the matrix. Then, the cutting state of SiC reinforced particles was analyzed, the novel appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…One is caused by the cutting edge making direct contact with the particle, while the other is caused by the tool and particle interacting indirectly with the matrix. Laghari et al [ 12 ] quantitatively examined the impact of interfacial characteristics on the strengthening effect of SiCp/Al composites by adding an interfacial layer to a single particle cutting simulation model. It is demonstrated that the stiff interface model had a stronger enhancing impact than the flexible interface model as the thickness of the interface increased.…”
Section: Introductionmentioning
confidence: 99%
“…One is caused by the cutting edge making direct contact with the particle, while the other is caused by the tool and particle interacting indirectly with the matrix. Laghari et al [ 12 ] quantitatively examined the impact of interfacial characteristics on the strengthening effect of SiCp/Al composites by adding an interfacial layer to a single particle cutting simulation model. It is demonstrated that the stiff interface model had a stronger enhancing impact than the flexible interface model as the thickness of the interface increased.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the researches on cutting of difficult-to-machine materials are particularly important. Since there is more cutting heat during the cutting process, the temperature in the cutting zone is higher, which leads to cutting to a certain extent [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Al-Si alloys are widely used as lightweight materials in aerospace, automotive parts, and other fields due to their excellent casting properties, high strength, and strong corrosion resistance [ 1 , 2 ]. SiCp has the characteristics of isotropy, low expansion coefficient, and high strength, which are ideal reinforcing materials for preparing metal matrix composites [ 3 , 4 ]. SiCp/Al-Si composites combine the advantages of SiC and Al-Si alloys in strength, expansion, and wear resistance [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%